Luminescent Immunoprecipitation System (LIPS) for Detection of Autoantibodies Against ATP4A and ATP4B Subunits of Gastric Proton Pump H+, K+‐ATPase in Atrophic Body Gastritis Patients. Issue 1 (January 2017) - Lahner, Edith; Brigatti, Cristina; Marzinotto, Ilaria; Carabotti, Marilia; Scalese, Giulia; Davidson, Howard W; Wenzlau, Janet M; Bosi, Emanuele; Piemonti, Lorenzo; Annibale, Bruno; Lampasona, Vito
Abstract : OBJECTIVES: : Circulating autoantibodies targeting the H+/K+‐ATPase proton pump of gastric parietal cells are considered markers of autoimmune gastritis, whose diagnostic accuracy in atrophic body gastritis, the pathological lesion of autoimmune gastritis, remains unknown. This study aimed to assess autoantibodies against ATP4A and ATP4B subunits of parietal cells H+, K+‐ATPase in atrophic body gastritis patients and controls. METHODS: : One‐hundred and four cases with atrophic body gastritis and 205 controls were assessed for serological autoantibodies specific for ATP4A or ATP4B subunits using luminescent immunoprecipitation system (LIPS). Recombinant luciferase‐reporter‐fused‐antigens were expressed by in vitro transcription‐translation (ATP4A) or after transfection in Expi293F cells (ATP4B), incubated with test sera, and immune complexes recovered using protein‐A‐sepharose. LIPS assays were compared with a commercial enzyme immunoassay (EIA) for parietal cell autoantibodies. RESULTS: : ATP4A and ATP4B autoantibody titers were higher in cases compared to controls ( P <0.0001). The area under the receiver‐operating characteristic curve was 0.98 (95% CI 0.965–0.996) for ATP4A, and 0.99 (95% CI 0.979–1.000) for ATP4B, both higher as compared with that of EIA: 0.86 (95% CI 0.809–0.896), P <0.0001. Sensitivity‐specificity were 100–89% for ATP4A and 100–90% for ATP4B assay. Compared with LIPS, EIA for parietal cell autoantibodies showed a lower sensitivity (72%, P <0.0001) at a similar specificity (92%, P =0.558). CONCLUSIONS: : Positivity to both, ATP4A and ATP4B autoantibodies is closely associated with atrophic body gastritis. Both assays had the highest sensitivity, at the cost of diagnostic accuracy (89 and 90% specificity), outperforming traditional EIA. Once validated, these LIPS assays should be valuable screening tools for detecting biomarkers of damaged atrophic oxyntic mucosa.